This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Chapter 8 Exponential functions 8.1 Graph the following functions: (a) f ( x ) = x 2 e x (b) f ( x ) = ln( x 2 + 3) (c) f ( x ) = ln( e 2 x ) 8.2 Express the following in terms of base e : (a) y = 3 x (b) y = 1 7 x (c) y = 15 x 2 +2 Express the following in terms of base 2: (d) y = 9 x (e) y = 8 x (f) y = e x 2 +3 Express the following in terms of base 10: (g) y = 21 x (h) y = 1000 10 x (i) y = 50 x 2 1 v.2005.1  September 4, 2009 1 Math 102 Problems Chapter 8 8.3 Compare the values of each pair of numbers (i.e. indicate which is larger): (a) 5 . 75 , 5 . 65 (b) 0 . 4 . 2 , . 4 . 2 (c) 1 . 001 2 , 1 . 001 3 (d) 0 . 999 1 . 5 , . 999 2 . 3 8.4 Rewrite each of the following equations in logarithmic form: (a) 3 4 = 81 (b) 3 2 = 1 9 (c) 27 1 3 = 1 3 8.5 Solve the following equations for x : (a) ln x = 2 ln a + 3 ln b (b) log a x = log a b 2 3 log a c 8.6 Reflections and transformations What is the relationship between the graph of y = 3 x and the graph of each of the following functions? (a) y = 3 x (b) y = 3 x (c) y = 3 1 x (d) y = 3  x  (e) y = 2 · 3 x (e) y = log 3 x 8.7 Solve the following equations for x : (a) e 3 2 x = 5 (b) ln(3 x 1) = 4 (c) ln(ln( x )) = 2 (d) e ax = Ce bx , where a negationslash = b and C > 0. v.2005.1  September 4, 2009 2 Math 102 Problems Chapter 8 8.8 Find the first derivative for each of the following functions: (a) y = ln(2 x + 3) 3 (b) y = ln 3 (2 x + 3) (c) y = ln(cos 1 2 x ) (d) y = log a ( x 3 2 x ) (Hint : d dx (log a x ) = 1 x ln a ) (e) y = e 3 x 2 (f) y = a 1 2 x (g) y = x 3 · 2 x (h) y = e e x (i) y = e t e t e t + e t 8.9 Find the maximum and minimum points as well as all inflection points of the following functions: (a) f ( x ) = x ( x 2 4) (b) f ( x ) = x 3 ln( x ) , x > (c) f ( x ) = xe x (d) f ( x ) = 1 1 x + 1 1+ x , 1 < x < 1 (e) f ( x ) = x 3 3 √ x (f) f ( x ) = e 2 x e x...
View
Full
Document
This note was uploaded on 05/19/2011 for the course MATH 102 Math 102 taught by Professor Allard during the Winter '09 term at UBC.
 Winter '09
 Allard

Click to edit the document details